Determined to fail: the role of genetic mechanisms in heart failure - Kayvanpour, Elham; Katus, Hugo; Meder, Benjamin (Current heart failure reports, 2015)
Genetic variants contribute to several steps during heart failure pathophysiology. The mechanisms include frequent polymorphisms that increase the susceptibility to heart failure in the general population and rare variants as causes of an underlying cardiomyopathy. In this review, we highlight recent discoveries made by genetic approaches and provide an outlook onto the role of epigenetic modifiers of heart failure.
Gesehen am 07.07.2020